1994
DOI: 10.1111/j.1365-2761.1994.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunodiagnosis of virulent strains of Aeromonas hydrophila associated with epizootic ulcerative syndrome (EUS) using a monoclonal antibody

Abstract: A virulent strain of Aeromonas hydrophila associated with epizootic ulcerative syndrome (EUS) was used to produce monoclonal antibodies that identified virulent strains of A. hydrophila. Antibodies from a clone, designated as F26P5C8, were found to identify the A. hydrophila serotype I isolates associated with EUS fish, and which were found to be virulent after subsequent inoculation studies. Immunodiagnosis of a large number of A. hydrophila from Australia and Japan showed some additional isolates to be ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…MAbs specific to A. hydrophila (groups 6 and 7) could recognize most of the A. hydrophila isolates obtained from both patients and aquatic animals, except for one isolate, AH7 (obtained from a patient), that displayed distinct biochemical reactions and immunoreactivities (Table 3). In the previous two reports, only one MAb was present; the MAb F26P5C8, specific to the LPS of A. hydrophila , which recognized only some virulent and non‐virulent isolates of A. hydrophila isolated from diseased and healthy fish from Malaysia and the Philippines (12/34 isolates), Japan (2/34 isolates), Australia (10/70 isolates) and human diarrhoea (4/9 isolates) (Cartwright et al. 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MAbs specific to A. hydrophila (groups 6 and 7) could recognize most of the A. hydrophila isolates obtained from both patients and aquatic animals, except for one isolate, AH7 (obtained from a patient), that displayed distinct biochemical reactions and immunoreactivities (Table 3). In the previous two reports, only one MAb was present; the MAb F26P5C8, specific to the LPS of A. hydrophila , which recognized only some virulent and non‐virulent isolates of A. hydrophila isolated from diseased and healthy fish from Malaysia and the Philippines (12/34 isolates), Japan (2/34 isolates), Australia (10/70 isolates) and human diarrhoea (4/9 isolates) (Cartwright et al. 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that these MAbs can be used for the simple and direct detection of A. hydrophila and Aeromonas spp. in infected fish by dot blotting without sample treatment or isolation of the bacteria, as required in an ELISA (Cartwright et al. 1994; Delamare et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation